Sunset trail : a western duo - Overholser, Wayne D.; Overholser, Wayne D. 1906-1996. (Waterville, Me. Five Star, 2007)
A U.S. agent must prevent a shipment of rifles from reaching the Comanche in New Mexico. Surrounded by enemies and accused of murder, he'll be lucky to make it to Santa Fe alive. And in Twelve Hours Till Noon, the people of Amity, Colorado, are stunned at the robbery of their local bank. But little do they know the "robbery" is only a cloak for a much bigger plan: assassinating the governor. The clock counts down as the tension rises
Sunset trail -- Twelve hours till noon.
"A Five Star Western"--T.p. verso.
"Published in conjunction with Golden West Literary Agency"--T.p. verso.
88848
Keywords: Western stories; Frontier and pioneer life